2021
DOI: 10.1186/s12887-021-02583-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with neurodevelopment in preterm infants with systematic inflammation

Abstract: Background Several studies have suggested that adverse neurodevelopment could be induced by systemic inflammation in preterm infants. We aimed to investigate whether preterm infants with systemic inflammation would have impaired neurodevelopment and which biomarkers and neurophysiologic studies during inflammation are associated with poor neurodevelopment. Methods This prospective cohort study enrolled infants born before 30 weeks of gestation or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Survival of very low birth weight (VLBW) infants has increased over the last few decades; however, poor postnatal growth and suboptimal neurodevelopmental outcomes are common in this population compared to the infants born at term [1][2][3]. Preterm birth alters brain development and multiple factors have been shown to have an impact on neurological outcomes: preexisting conditions, size at birth [4], gestational age (GA) [5], nutrition and postnatal growth faltering [6], and comorbidities [7][8][9][10]. Preterm infants are born during a period of rapid fetal growth, requiring high nutrient intake to promote extrauterine growth.…”
Section: Introductionmentioning
confidence: 99%
“…Survival of very low birth weight (VLBW) infants has increased over the last few decades; however, poor postnatal growth and suboptimal neurodevelopmental outcomes are common in this population compared to the infants born at term [1][2][3]. Preterm birth alters brain development and multiple factors have been shown to have an impact on neurological outcomes: preexisting conditions, size at birth [4], gestational age (GA) [5], nutrition and postnatal growth faltering [6], and comorbidities [7][8][9][10]. Preterm infants are born during a period of rapid fetal growth, requiring high nutrient intake to promote extrauterine growth.…”
Section: Introductionmentioning
confidence: 99%
“…Meeting nutritional demands through enteral feeding after birth is constrained by the immaturity of the gut in preterm infants, meaning they are prone to poor growth and development in early life (Zozaya et al, 2019). Furthermore, preterm infants have an increased risk of being exposed to inflammation, either prenatally or postnatally, which impairs neurodevelopment (Cappelletti et al, 2016; Lee et al, 2021). Prematurity therefore has long‐term consequences on the health and cognitive development of individuals into adulthood (Kajantie et al, 2010; MacKay et al, 2010; Markopoulou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“… 29 , 30 Studies in preterm infants have reported an association between postnatal growth restriction of the head circumference and adverse developmental outcomes. 31 33 Hence, it was reassuring that postnatal growth restriction for head circumference was less severe in the probiotic group in our RCT. Similar beneficial effects of probiotics on head circumference were observed in extremely low birth weight infants in recent RCTs.…”
Section: Discussionmentioning
confidence: 61%